2012
DOI: 10.1080/14786435.2012.687841
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent formation and shrinkage of hollow shells in hemispherical Ag/Pd nanoparticles

Abstract: It is shown that both the growth and shrinkage of hollow shells in Ag/Pd hemispherical core-shell nano structures took place at the same temperature. The crossover time, t cr , between these regimes is shifted to smaller values with increasing temperatures. This result confirms that the growth and the shrinkage regimes are controlled by the faster as well as the slower diffusion coefficients (D Ag as well as D Pd ), respectively. The pore radius, confirming recent theoretical predictions, linearly depends on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
5
11
1
Order By: Relevance
“…Table 1 shows the real saturation compositions (as calculated by the use of Equation 3) too and the values of the D Ag /D Au ratios, estimated using the initial conditions of c A0 = c B0 = 0. It can be seen that in the Ag/Au/substrate system these ratios, as calculated from Equation 1 and Equation 2, are between 4 and 1.5, in good accordance with the conclusions obtained in [24], and are the same in Au and Ag, i.e., they do not depend on the composition. Furthermore, although the experimental errors of the estimated ratios can be high (the uncertainty can be about 50% and 20% at the lowest and highest temperatures, respectively), the temperature dependence of this ratio has also the correct sign.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Table 1 shows the real saturation compositions (as calculated by the use of Equation 3) too and the values of the D Ag /D Au ratios, estimated using the initial conditions of c A0 = c B0 = 0. It can be seen that in the Ag/Au/substrate system these ratios, as calculated from Equation 1 and Equation 2, are between 4 and 1.5, in good accordance with the conclusions obtained in [24], and are the same in Au and Ag, i.e., they do not depend on the composition. Furthermore, although the experimental errors of the estimated ratios can be high (the uncertainty can be about 50% and 20% at the lowest and highest temperatures, respectively), the temperature dependence of this ratio has also the correct sign.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast to the Ag/Au/substrate systems, where the agreement with the step model of GB motion during DIGM is very good, there is a qualitative agreement only for the results obtained in Ag(15 nm)/Pd(15 nm)/substrate films. Qualitative agreement means that the larger saturation value of Ag in Pd (as compared to that of the Pd in Ag) is in accordance with the fact that D Ag /D Pd > 1 [24]. On the other hand reversing the film sequence the inequality of the saturation values reversed too: this is in contrast to the expectations based on Equation 1 and Equation 2.…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, lattice vacancies in the nanostructures with large lateral dimensions have a high tendency to nucleate into voids before they can diffuse out . This size‐dependent geometric evolution of nanostructures in the delithiation process agrees with theoretical modeling . The surface diffusion of lithium can be suppressed by coating the nanostructures with an amorphous Si layer, preventing the formation of voids .…”
Section: In Situ Electron Microscopy Characterizationsupporting
confidence: 76%
“…[103] This size-dependent geometric evolution of nanostructures in the delithiation process agrees with theoretical modeling. [82,104] The surface diffusion of lithium can be suppressed by coating the nanostructures with an amorphous Si layer, preventing the formation of voids. [20] A similar hollowing mechanism was also observed in the delithiation of Li x Si, where the formation of porous structures can be suppressed by coating the nanostructures with a layer of alucone with fast conductivity to Li + and eto balance the mass of diffusion.…”
Section: In Situ Electron Microscopy Characterizationmentioning
confidence: 99%
“…The above differences in the compositions on the two sides of the above couples also means that, using techniques having resolution of about 1 atom %, there is a hope to observe DIGM on both sides only if the D A / D B ratio is not larger than 20. In two of our previous papers, investigating the formation and shrinkage of hollow shells in hemispherical Ag/Au and Ag/Pd systems between 430 and 470 °C [ 23 24 ], it was concluded that the D Ag / D Au ratio should be about five times larger than unity, while D Ag / D Pd should be larger by at least one order of magnitude than this value.…”
Section: Discussionmentioning
confidence: 99%